The Discriminatory Compulsory Retirement Age in Brazil - de Carvalho, Marco Cesar (2015)
This article shows that, after the Constitution of 1988, Social Security has evolved in Brazil, where its goals corroborate the objectives of the Republic, through a constant process of political and social reform in its composition. However, as only the prediction of social rights not just himself, requiring further the effective implementation of these, especially because they are fundamental rights, for the protection of the elderly. It is undeniable that there are flaws in the welfare rights of the elderly, and the current age limit for retirement, both the private sector and the public, does not match reality stamped in the growing life expectancy of the brazilian person, deserving fixes for such suitability for which are proposed legislative changes to even encourage the hiring of older people by companies. Therefore, this study is underpinned by statistical data and references indicated to an end.